(untitled) (Czech Journal of Multidisciplinary Innovations, 2025)
Performance evaluation is a current topic in most administrations around the world, both in the East and the West. It is not surprising that financial analysis is often presented as one of the primary evaluation tools in many cases. Since performance evaluation frequently focuses on profits and financial revenues, assessing performance using financial analysis gains importance and becomes one of the clearest means to achieve accuracy and determine the extent of profitability. When we turn to financial analysis itself, nothing is more indicative of it, as its tools and methods reflect the means used in the analysis.